Renovatio imperii - Corona Hungariae regia (Idea Europae unitae in opusculo Sancti Stephani, quod "Libellus de institutione morum sive admonitio spiritualis" inscribitur) - Havas, László (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
No abstract is available for this article, published in Acta Classica Universitatis Scientiarum Debreceniensis, Issue XLII, 2006. At the time of publication, abstracts were not required from the authors. Please consult the full text for further details.